2006
DOI: 10.1111/j.1467-8578.2006.00415.x
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion – the heart of the matter: trainee teachers' perceptions of a parent's journey

Abstract: The importance of parental choice, and parents' participation in educational processes, continue to be highlighted in strategies, acts and policies around the world. Partnership with parents is given an even higher profile in relation to educational opportunities for children with special needs. Yet many trainee teachers have only limited understandings of the impact on family life of a child with special needs; are uncertain how best to work with parents; and are not confident about the choices that parents m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 13 publications
(16 reference statements)
1
32
0
2
Order By: Relevance
“…Murray et al The value of parent/professional partnerships in education is well-established and is reflected in the laws, policies, and professional guidelines for educators. The components of familycentered practices are embedded in The Individuals with Disabilities Education Act (IDEA) as well as the No Child Left Behind Act (NCLB) and various other government policies in the United States and around the world (Chavkin, 2005;Epstein & Sanders, 2006;Forlin & Hopewell, 2006;Pinkus, 2005). Familycentered practices are also included in recommended practices of the Council of Exceptional Children, the Division of Early Childhood, and the National Association for the Education of Young Children (Hyson, 2003).…”
mentioning
confidence: 98%
“…Murray et al The value of parent/professional partnerships in education is well-established and is reflected in the laws, policies, and professional guidelines for educators. The components of familycentered practices are embedded in The Individuals with Disabilities Education Act (IDEA) as well as the No Child Left Behind Act (NCLB) and various other government policies in the United States and around the world (Chavkin, 2005;Epstein & Sanders, 2006;Forlin & Hopewell, 2006;Pinkus, 2005). Familycentered practices are also included in recommended practices of the Council of Exceptional Children, the Division of Early Childhood, and the National Association for the Education of Young Children (Hyson, 2003).…”
mentioning
confidence: 98%
“…Therefore, teacher education programs should ensure that candidates have access to these opportunities that allow them to build on the confidence in this new knowledge and ultimately enhance the parent-professional partnership (Murray & Mandell, 2006). Previous research (Epstein, 2005;Forlin & Hopewell, 2006;Hoover-Dempsey et al, 2002;Pinkus, 2005) indicates that establishing relationships with families can be difficult for teachers. Moreover, the same literature suggests that shifting those perceptions toward constructive views on collaboration with families can be challenging.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, teachers who complete their teacher education programs feeling ill-equipped to teach children with special learning needs may demonstrate a reluctance to teach in inclusive settings (Jordan, Schwartz, & McGhie-Richmond, 2009) and may hamper progress in schools as it relates to inclusive education (Atkinson, 2004;Forlin, Loreman, Sharma & Earle, 2009). Given that the attitudes of in-service teachers are dependent on local culture and considering that changing the attitudes of these teachers is a complex political endeavor (Symeonidou & Phtiaka, 2009), Forlin and Hopewell (2006) and Andrews (2002) suggested that teacher preparation programs have a role to play in fostering attitudes that support inclusion. Furthermore, White (2007) showed that very little change in teacher attitudes toward inclusion occurs within their first five years of teaching, suggesting teacher education programs might be best places to develop these desired attitudes.…”
Section: Attitudinal Factorsmentioning
confidence: 99%